TYTO ALBA INOVASI PENGENDALI HAMA TIKUS (Rattus argentiventer) MELALUI PEMBERDAYAAN PETANI PADI SAWAH - Sonia Berliani; Wida Pradiana; Wahyu Trisnasari (Jurnal Inovasi Penelitian, 2021)
Field rats are the main pests of rice plants with the highest level of puso attack, the area of attack by field rats in Garut Regency reaches 1,200 ha or reaches 20-30% of the damage suffered. Controls that are usually carried out by farmers have not shown optimal results and if it is carried out in the long term, it will have a negative impact on the environment. It is necessary to have alternative control techniques that are environmentally friendly, namely by utilizing natural enemies in the form of owls. This study aims to analyze the level of farmer empowerment, analyze the factors that influence farmer empowerment in rat pest control, determine the right strategy in the application of rat pest control, and analyze the effectiveness of owls in controlling rat pests. Data collection in this study was carried out through interviews and giving questionnaires. Descriptive analysis was carried out to analyze farmer empowerment, regression analysis was used to determine the effect of farmer characteristics and external factors on farmer empowerment, descriptive analysis was used to design appropriate strategies for farmer empowerment in rat pest control, and analysis of the effectiveness of owl utilization (Tyto alba). using the n-gain test and independent sample t test. The results of the analysis show that the farmers' knowledge is at a moderate level. The design of the farmer empowerment strategy is to provide information about the benefits of natural enemies and create a demonstration plot. Control of field mice by using owls can be said to be effective